A multi-agent system using fuzzy logic applied to e-health in order to monitor hypertension - Lima Neto, Afonso Bezerra (2018)
As time is passing by, life quality is becoming one of the most concerns for people who are getting old. According to studies involving countries in Europe, older people tend to live alone or, at most, with another person. The technology, currently available considering health products, helps those people to achieve their goals. However, the solutions that contain this technology still have a generic and proprietary character of each manufacturer, not allowing the integration with other solutions with open architecture, in order to generate a better use of the captured data, and to identify problems from other perspectives. Taking that into account, this work proposes a multi-agent system architecture that uses IoT devices to catch patients heart signals and, using artificial intelligence through fuzzy logic process to estimate the level of hypertension, considering systolic pressure, diastolic pressure, age, and body mass index. We used information about 768 patients obtained from a public database and evaluated the performance of the presented fuzzy logic model. The proposed solution compared the results of such fuzzy logic with an evaluation made by nurses, reaching a 94.40% of accuracy in the diagnosis.  Keywords: Fuzzy logic. Multi-agent system. Health. IoT